Characterization and impact of COVID‐19‐tested and infected patients: Experience of The Johns Hopkins Health System Regional Emergency Departments. Issue 1 (8th December 2020) - Kelen, Gabor D.; Swedien, Daniel; Hansen, Jonathan; Klein, Eili; Peterson, Susan; Saheed, Mustapha; Scheulen, Jim; Mann, Edana
Abstract: Background: There is limited understanding of the characteristics and operational burden of persons under investigation (PUIs) and those testing positive for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) presenting to emergency departments (EDs). Methods: We reviewed all adult ED visits to 5 Johns Hopkins Health System hospitals in the Maryland/District of Columbia (DC) region during the initial coronavirus disease 2019 (COVID‐19) surge, analyzing SARS‐CoV‐2 polymerase chain reaction test eligibility, results, demographics, acuity, clinical conditions, and dispositions. Results: Of 27, 335 visits, 11, 402 (41.7%) were tested and 2484 (21.8%) were SARS‐CoV‐2 positive. Test‐positive rates among Hispanics, Asians, African Americans/Blacks, and Whites were 51.6%, 23.7%, 19.8%, and 12.7% respectively. African American/Blacks infection rates (25.5%–33.8%) were approximately double those of Whites (11.1%–21.1%) in the 3 southern Maryland/DC EDs. Conditions with high test‐positive rates were fever (41.9%), constitutional (36.4%), upper respiratory (36.9%), and lower respiratory (31.2%) symptoms. Test‐positive rates were similar in all age groups (19.9% to 25.8%), although rates of hospitalization increased successively with age. Almost half, 1103 (44.4%), of test‐positive patients required admission, of which 206 (18.7%) were to an ICU. Conclusion: The initial surge of SARS‐CoV‐2 test‐positive patients experienced in a regional hospital system had ≈ 42% of patients meeting testing criteria and nearly one‐fifth of those testing positive. The operational burden on ED practice, including intense adherence to infection control precautions, cannot be understated. Disproportionately high rates of infection among underrepresented minorities underscores the vulnerability in this population. The high rate of infection among self‐identified Asians was unexpected.